Exploration of school administrators’ experiences on perceiving left-behind children in China - Omar, Muhd Khaizer; Wang, Yifan; Yang, Mengmeng (Human Resource Management Academic Research Society, 2024)
The purpose of this study is to deal with the increasingly serious challenge of left-behind children in China under the rapid development of China's society and focus on building specific improvement measures and operable countermeasures to solve the educational and psychological problems of rural Left-behind children in China. To achieve this goal, the research adopted a qualitative phenomenological research method to explore the views and experiences of professionals in related fields on the issue of Left-behind children in China. This study focuses on the situation of Left-behind children in rural areas in China. Through interviews, the researchers conduct face-to-face or online interviews with school administrators, psychologists, and practitioners in other relevant fields to obtain their unique views and experiences on the education and psychological problems of Left-behind children in China. The interview employed open-ended questions and encouraged respondents to express their thoughts and stories plainly, to reveal specific measures and effective countermeasures to solve the problem. By collecting and carefully analyzing interview data, we extracted key themes and models to deeply understand the role and contribution of education administrators and professionals in promoting the education and psychological health of rural Left-behind children in China. The results of the study provide empirical support for the development of specific improvement measures and operational countermeasures for Left-behind children in China and offer useful guidance and suggestions for relevant decision-makers and practitioners. Through this study, we hope to provide practical insights and solutions to the educational and psychological problems of rural Left-behind children in China. At the same time, this study suggests references for social managers, educators, and researchers in China and other similar regions to jointly address the problem of Left-behind children in China and flourish their comprehensive development and healthy growth.